How to eat : the pleasures and principles of good food - Lawson, Nigella (London Chatto & Windus, 2014)
With witty food writing, easy recipes, basic cooking tips and a hardback design, this book covers: Basics - from easy bread recipes and basic roast chicken to sauce ingredients and seasonal foods; Fast food - easy recipes and quick meal ideas, and Weekend lunch - Saturday and Sunday lunch menus.
Keywords: Cookery